A simple, rapid method for the extraction of whole fire ant venom (Insecta: Formicidae: Solenopsis) - Gonçalves Paterson Fox, Eduardo (2013)
The invasive fire ant Solenopsis invicta is medically important because its venom is highly potent. However, almost nothing is known about fire ant venom proteins because obtaining even milligram-amounts of these proteins has been prohibitively challenging. We present a simple and fast method of obtaining whole venom compounds from large quantities of fire ants. For this, we separate the ants are from the nest soil, immerse them in dual-phase mixture of apolar organic solvent and water, and evaporate each solvent phase in separate. The remaining extract from the aqueous phase is largely made up of ant venom proteins. We confirmed this by using 2D gel electrophoresis while also demonstrating that our new approach yields the same proteins obtained by other authors using less efficient traditional methods. © 2013 Elsevier Ltd.